Design of a Website-Based Project Management Information System at Warung Nasi Kak Jum Saridah - Maulidya Putri Kinanti Ritonga; Yahfizham Yahfizham (JUSTINFO | Jurnal Sistem Informasi dan Teknologi Informasi, 2023)
Concept, testing, and service are the main priorities in the Warung Nasi Kak Jum Saridah business. Considering the use of paper media in order recording, table monitoring, and product data systems, problems often arise such as data duplication, misplaced documents, and errors in orders. Therefore, to overcome this problem, Warung Nasi Kak Jum Saridah needs a cashier management information system. This system will help business owners manage product data, monitor the dining table, and manage transactions more efficiently. Prototype analysis using the waterfall method in developing the cashier management information system at Warung Nasi Kak Jum Saridah. The hope is that this system will facilitate the overall cashier supervision and management process, increase efficiency in daily operations, and reduce errors that often occur in recording and monitoring data. Thus, the implementation of the cashier management information system will have a positive impact on the productivity and quality of Warung Nasi Kak Jum Saridah services to customers.